Historic Environment Education – Vaal River tunnels: The forgotten history of the early days of coal in the Vereeniging area (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article describes a part of the history of coal in the Vereeniging area which has, as far as could be determined, not been documented in detail before. Information was obtained from written primary and secondary as well as oral sources. In the article it is also explained how this content can be integrated into Social Sciences, History and Geography teaching as part of historic environment education.
Keywords: Historic environment; GW Stow; Tunnels; Discovery of coal; Time travel; Vaal River